Physical agents in rehabilitation : an evidence-based approach to practice - Cameron, Michelle H. (St. Louis, Missouri : Elsevier, 2018)
Provides support for how physical agent modalities are discussed in the classroom and used in clinical rehabilitation practice to improve patient outcomes. This new edition brings the ideal balance of evidence and practical instruction to the learning and practice of physical agents in rehabilitation.
Introduction to physical agents. The physiology of physical agents -- Physical agents in clinical practice -- Pathology and patient problems. Inflammation and tissue repair -- Pain and pain management -- Tone abnormalities -- Motion restrictions -- Thermal agents. Introduction to thermal agents -- Superficial cold and heat -- Ultrasound -- Diathermy -- Electrical currents. Introduction to electrotherapy -- Electrical currents for muscle contractions -- Electrical currents for pain control -- Electrical currents for soft tissue healing -- Electromyographic (EMG) Biofeedback -- Electromagnetic Agents. Lasers and light -- Ultraviolet therapy -- Mechanical agents. Hydrotherapy -- Traction -- Compression.
Includes bibliographical references and index.
Keywords: Physical Therapy Modalities; Physical Therapy Modalities -- instrumentation; Rehabilitation -- methods; Evidence-Based Practice; Physical therapy; Medicine, Physical